Characteristics and outcomes of patients screened for transcatheter mitral valve implantation: 1‐year results from the CHOICE‐MI registry. (17th April 2022) - Ben Ali, Walid; Ludwig, Sebastian; Duncan, Alison; Weimann, Jessica; Nickenig, Georg; Tanaka, Tetsu; Coisne, Augustin; Vincentelli, Andre; Makkar, Raj; Webb, John G.; Akodad, Mariama; Muller, David W.M.; et al.
Abstract : Aims: Transcatheter mitral valve implantation (TMVI) represents a novel treatment option for patients with mitral regurgitation (MR) unsuitable for established therapies. The CHOICE‐MI registry aimed to investigate outcomes of patients undergoing screening for TMVI. Methods and results: From May 2014 to March 2021, patients with MR considered suboptimal candidates for transcatheter edge‐to‐edge repair (TEER) and at high risk for mitral valve surgery underwent TMVI screening at 26 centres. Characteristics and outcomes were investigated for patients undergoing TMVI and for TMVI‐ineligible patients referred to bailout‐TEER, high‐risk surgery or medical therapy (MT). The primary composite endpoint was all‐cause mortality or heart failure hospitalization after 1 year. Among 746 patients included (78.5 years, interquartile range [IQR] 72.0–83.0, EuroSCORE II 4.7% [IQR 2.7–9.7]), 229 patients (30.7%) underwent TMVI with 10 different dedicated devices. At 1 year, residual MR ≤1+ was present in 95.2% and the primary endpoint occurred in 39.2% of patients treated with TMVI. In TMVI‐ineligible patients ( n = 517, 69.3%), rates of residual MR ≤1+ were 37.2%, 100.0% and 2.4% after bailout‐TEER, high‐risk surgery and MT, respectively. The primary endpoint at 1 year occurred in 28.8% of patients referred to bailout‐TEER, in 42.9% of patients undergoing high‐risk surgery and in 47.9% of patients remaining on MT. Conclusion: This registry included the largest number of patients treated with TMVI to date. TMVI with 10 dedicated devices resulted in predictable MR elimination and sustained functional improvement at 1 year. In TMVI‐ineligible patients, bailout‐TEER and high‐risk surgery represented reasonable alternatives, while MT was associated with poor clinical and functional outcomes. Abstract : Results from the global CHOICE‐MI registry. CHOICE‐MI, CHoice of OptImal transCatheter trEatment for Mitral Insufficiency; HF, heart failure; MAC, mitral annulus calcification; MR, mitral regurgitation; MVPG, mitral valve pressure gradient; TEER, transcatheter edge‐to‐edge repair.